Effects of Peer Influences and Life-History Strategy on Chinese Junior High School Students’ Prosocial and Antisocial Behaviors - Zhu, Nan; Lu, Hui J.; Chang, Lei (Frontiers in Education, 2020)
Peer influence and life-history strategy have been shown in previous research as facilitators of adolescents’ social conduct. The current research uses the data from a two-wave, nationally representative survey of Chinese junior high school students to examine how different aspects of peer influence and life-history strategy in Grade 7 might contribute to prosocial and antisocial behaviors in Grade 8. We also considered differences between local and migrant students. The results showed that friend prestige predicted more prosocial behaviors and less antisocial behaviors, whereas friend deviancy predicted less prosocial behaviors and more antisocial behaviors. Moreover, the facilitating effect of friend deviancy on antisocial behaviors was amplified in migrant students more than for local students. Slow life-history strategy predicted more prosocial behaviors and, especially for migrant students, less antisocial behaviors. These findings indicate adolescents’ migrant backgrounds deserve extra attention when investigating peer influence and life-history strategy as distinct contributors to adolescents’ social conduct.